Asymmetric effects of voluntary disclosure on stock liquidity: evidence from 8‐K filings. (3rd January 2020) - Cho, Hyunkwon; Kim, Robert
Abstract: This paper examines whether the change in stock liquidity subsequent to voluntary disclosure is different between good news and bad news. Using voluntary 8‐K filings, we find that the increase in stock liquidity is more pronounced for firms with good news disclosure than for firms with bad news disclosure. In addition, such findings are stronger when a firm is less visible and when the short‐selling costs are high, suggesting that these two factors play an important role in increasing stock liquidity. Overall, this paper provides evidence that the tone of voluntary 8‐K news is an important determinant of stock liquidity.